Proses Penyelesaian Sengketa Gugatan Lelang Kepemilikan Sertifikat Hak Milik Nasabah terhadap PT. Bank Panin Indonesia (Studi Putusan No: 209/Pdt.G/2019/PN Tjk) - Erlina Erlina; Risti Dwi Ramasari; Rizky Ananda (Universitas Batanghari Jambi, 2021)
Bank is a financial institution that plays an important role in a country's economy. Credit is a loan that is submitted to buy something and the borrower makes payments by installments in accordance with applicable regulations. One of the things that is required by banks as creditors in providing credit is protection in the form of guarantees that must be provided by the debtor to ensure repayment of their debts for security and legal certainty. Basically the creditor holding the material guarantee has the right to execute collateral for sale by auction for debtor debt payment if the debtor fails to carry out his obligations based on a credit agreement or commonly referred to as default One of the dispute over a certificate ownership auction between the debtor or customer and the creditor or banking institution to be precise between the customer and PT Bank Panin Indonesia with decision number 209 / Pdt.G / 2019 / PN Tjk. The problem in this research is whether the factors that cause it to occur and how is the process of dispute resolution on the auction claim ownership certificate of customer ownership against PT Bank Panin Indonesia. This study uses a juridical normative and empirical juridical research approach. In this study using secondary data sources and primary data. Data collection techniques used through literature study, observation and interviews. Qualitative juridical data analysis. That the factors causing the dispute over the Auction of Customer's Ownership Certificate Ownership against PT Bank Panin Indonesia studied on Decision Number 209 / Pdt.G / 2019 / PN Tjk in which the Plaintiff was a Debtor to the Defendant As a result of the Plaintiff being unable to pay the Credit that was given by PT Bank Panin Indonesia as the Creditor, an auction was conducted with a limit value of Rp. 1,470,000,000 (one billion four hundred seventy million rupiah). As a result of this, the Plaintiff stated that the Defendant had committed illegal acts which caused the loss of the Plaintiff. The Dispute Resolution process carried out through Non-Litigation does not produce results, then it is carried out through Litigation. The Lawsuit against the Law filed by the Plaintiff against PT Bank Panin Indonesia was declared unacceptable. It is recommended that the public, in particular, be able to better understand and take into account and consider applying for credit to banking institutions because they have the risk of losing assets that are guaranteed to banking institutions. For banking institutions to be able to provide a very clear explanation when a credit agreement is made to avoid a lawsuit due to a misunderstanding between the banking institution as the creditor against the debtor at a later date.